Otoritas Kepemimpinan Kyai Dalam Membentuk Budaya Organisasi Religius - Moh. Samsul Bahri (CV Edujavare Publishing, 2024)
Study This done For study leadership khodimul ceremony syubbanul Muslim with study type qualitative . Technique data collection used is interview in-depth, observation And documentation. In authority leadership traditional if get based legitimacy​ on existing trust​ established in A tradition in society. On the other side too has get legitimacy from the people who carry it out authority according to tradition the. In other words, authority traditional based on claim tradition that there is virtues stated​ by the leader And get trust from party follower based on the structural factors of the leader 's descent the. Whereas authority leadership charismatic own Power pull, energy And external demeanor​ normal For influence other people, so He own outside followers​ normal the amount ( quantity ) and very strong bodyguards ( followers ). loyal And obedient subserve to him without there is a reserve ( quality ). From existing research​ done, results research obtained​ is with​ use theory Max weber's authority, researcher find that khodimul ceremony syubbanul Muslim own Authority Traditional And Authority Charismatic.